Dialog Kehidupan Ayub Memproklamirkan Kemahakuasaan Allah dalam Bentuk Keadilan dan Kebenaran - Panjaitan, Firman; Purba, Novi Aling (STT Iman Jakarta, 2021)
God's justice and righteousness are central themes in living life. A life filled with God's justice and righteousness will bring happiness and prosperity. Therefore, God's justice and truth need to be dialogued so that a life filled with prosperity will be realized in real terms. However, it must be admitted that God's justice and truth are not easy to understand, therefore efforts are needed to continue to seek and find God so that humans can feel and realize God's justice and truth in life. The difficulty of understanding God's justice and righteousness is evident in the events of Job's suffering. Many opi-nions, based on an understanding of the theology of retribution, want to show that Job's suffering occurred because of Job's sinfulness. But actually, the incident of Job is a real example of God trying to dialogue His justice and truth with humans. By using a qualitative method that is realized in the form of a literature approach, this article would like to reveal that the incident of Job's suffering is God's way to invite people to be more submissive and enter into the continuous search for God. God's justice and truth need to be dialogued continuously so that humans understand God more correctly. AbstrakKeadilan dan kebenaran Allah merupakan salah satu tema sentral dalam menjalani kehidupan. Kehidupan yang dipenuhi keadilan dan kebenaran Allah akan mendatangkan kebahagiaan dan kesejahteraan. Oleh sebab itu keadilan dan kebenaran Allah perlu untuk didialogkan agar kehidupan yang dipenuhi dengan kesejahteraan akan terwujud secara nyata. Namun harus diakui bahwa keadilan dan kebenaran Allah tidaklah mudah untuk dipahami, karena itu dibutuhkan upaya untuk terus mencari dan menemukan Allah agar manusia dapat merasakan sekaligus mewujudnyatakan keadilan dan kebenaran Allah itu di dalam kehidupan. Sulitnya memahami keadilan dan kebenaran Allah tampak dalam peristiwa penderitaan Ayub. Banyak pendapat, dengan didasarkan pada pemahaman teologi retribusi, hendak menunjukkan bahwa penderitaan Ayub terjadi karena keberdosaan Ayub. Namun sebenarnya peristiwa Ayub merupakan contoh nyata dari Allah yang berupaya mendialogkan keadilan dan kebenaran-Nya kepada manusia. Dengan menggunakan metode kualitatif yang diwujudkan dalam bentuk pendekatan literatur, artikel ini hendak mengungkap bahwa peristiwa penderitaan Ayub merupakan cara Allah untuk mengajak manusia semakin tunduk dan masuk dalam upaya pencarian Allah dengan terus menerus. Keadilan dan kebenaran Allah perlu untuk didialogkan terus menerus, agar manusia semakin memahami Allah dengan benar.